2014
DOI: 10.1002/etc.2776
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phosphate on arsenic uptake and toxicity alleviation in tobacco genotypes with differing arsenic tolerances

Abstract: Phosphate (PO4 (3-) ) has been reported to suppress arsenate (As(v) ) uptake in plants. However, its effects on controlling the availability of As(v) in tobacco genotypes with different arsenic (As) tolerances has not been fully explored. In the present study, the effects of PO4 (3-) on As(v) uptake were investigated in a hydroponic culture using 2 tobacco (Nicotiana tabacum) genotypes (ZY90 and FSMY) that differed in As(v) tolerance. A total of 9 treatment combinations comprising As(v) treatments of 0 µM, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…These observations relate to the findings of the present study in which the exposed tobacco genotypes showed greater MDA content, which indicated high lipid peroxidation. Lead toxicity induces oxidative stress by accumulation of ROS . The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations relate to the findings of the present study in which the exposed tobacco genotypes showed greater MDA content, which indicated high lipid peroxidation. Lead toxicity induces oxidative stress by accumulation of ROS . The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids .…”
Section: Discussionmentioning
confidence: 99%
“…Lead toxicity induces oxidative stress by accumulation of ROS [8,[44][45][46]. The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids [1].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of key enzyme systems leads to the formation of ROS, which in turn causes lipid peroxidation [39]. Many previous studies have demonstrated that the tolerant plant varieties or genotypes have better ability of scavenging ROS by producing higher levels of antioxidants [26,28,34]. The high levels of SOD, CAT, and POD activities in gannuoxiang indicate efficient scavenging of superoxide radical and H 2 O 2 .…”
Section: Shoot Rootmentioning
confidence: 99%
“…Nicotiana tabacum is one of the most socially and economically important crops worldwide. It is not a hyperaccumulator of semimetals/metals although it is able to take and accumulate them at consistent level (Zvobgo et al 2015 ). In addition, it is a good candidate for phytoextraction because of its high biomass, moderate soil chemical/physical requirement, fast growth rate and easy to harvesting (Sarret et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%